Recent Trends in Fracture and Damage Mechanics - Hütter, Geralf; Zybell, Lutz (Springer International Publishing : Imprint: Springer, 2016)
This book covers a wide range of topics in fracture and damage mechanics. It presents historical perspectives as well as recent innovative developments, presented by peer reviewed contributions from internationally acknowledged authors.  The volume deals with the modeling of fracture and damage in smart materials, current industrial applications of fracture mechanics, and it explores advances in fracture testing methods. In addition, readers will discover trends in the field of local approach to fracture and approaches using analytical mechanics. Scholars in the fields of materials science, engineering and computational science will value this volume which is dedicated to Meinhard Kuna on the occasion of his 65th birthday in 2015. This book incorporates the proceedings of an international symposium that was organized to honor Meinhard Kuna's contributions to the field of theoretical and applied fracture and damage mechanics.